1982
DOI: 10.1159/000198833
|View full text |Cite
|
Sign up to set email alerts
|

Exocrine Pancreatic Function in Insulin-Dependent Diabetes mellitus

Abstract: Exocrine pancreatic function was studied in patients with long-standing insulin-dependent diabetes mellitus using the secretin-pancreozymin test (n = 53), and estimation of immunoreactive trypsin (n = 43) and pancreatic isoamylase (n = 43). The secretin-pancreozymin test was abnormal in 23 patients (43 %). The abnormalities found were a decreased output of lipase (37%), amylase (36%) or trypsin (26%) and bicarbonate (15%). Serum immunoreactive trypsin was below normal in only 6 (14%) and pancreatic isoamylase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0
7

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(73 citation statements)
references
References 6 publications
3
63
0
7
Order By: Relevance
“…Studies of the pancreatic exocrine gland of IDDM patients have reported an abnormal response to the secretin-pancreozymin test and a decreased output of lipase, amylase and trypsin [16,17]. We propose the following mechanism as a cause of decreased pancreatic exocrine function in IDDM patients: noticeably decreased secretion of insulin, a growth-promoting hormone, in the pancreas may impair the normal growth of the exocrine gland resulting in atrophy, fibrosis and fatty changes in the tissue.…”
Section: Discussionmentioning
confidence: 88%
“…Studies of the pancreatic exocrine gland of IDDM patients have reported an abnormal response to the secretin-pancreozymin test and a decreased output of lipase, amylase and trypsin [16,17]. We propose the following mechanism as a cause of decreased pancreatic exocrine function in IDDM patients: noticeably decreased secretion of insulin, a growth-promoting hormone, in the pancreas may impair the normal growth of the exocrine gland resulting in atrophy, fibrosis and fatty changes in the tissue.…”
Section: Discussionmentioning
confidence: 88%
“…This conclusion is substantiated by clinical studies on the exocrine secretory capacity of the pancreas in chronic Type I diabetes demonstrating decreased secretion of enzymes [32][33][34][35][36]. Frier et al found that the preservation of pancreatic function correlates with the duration of diabetes [32] and the persistence of B-cell secretory activity measured by C-peptide levels [33].…”
Section: Discussionmentioning
confidence: 91%
“…It has previously been reported that the pancreas of people with type 1 diabetes is characterised by increased fibrosis, small size and impaired exocrine function [3,7,8,33,34]. This has led to speculation that this might be due to a separate autoimmune process affecting the exocrine pancreas [35].…”
Section: Discussionmentioning
confidence: 99%